Introduction to Network Security - Deshpande, Abhinav V (International Journal of Computer Sciences and Engineering, 2025)
Network security is a complicated subject, historically only tackled by well-trained and experienced experts. However, as more and more people become “wired”, an increasing number of people need to understand the basics of security in a networked world. This document was written with the basic computer user and information systems manager in mind, explaining the concepts needed to read through the hype in the marketplace and understand risks and how to deal with them. Some history of networking is included, as well as an introduction to TCP/IP and internet working. We go on to consider risk management, network threats, firewalls, and more special-purpose secure networking devices. This is not intended to be a reference, nor is it a document describing how to accomplish specific functionality. It is hoped that the people will have a wider perspective on security in general, and better understand how to reduce and manage risk personally, at home, and in the workplace.